Reflections on sound timbre definitions - SANKIEWICZ, Marianna; BUDZYŃSKI, Gustaw (Archives of Acoustics, 2007)
The article is concerned with systematic classification of concepts and terms in acoustics. Special attention is attached to definitions of timbre. The article presents a review of definitions of timbre published in the literature. Inadequacy of the currently used IEC definition is shown and a new definition of timbre is proposed. Discussed are advantages of the new definition and the prospects for common acceptance of this definition in acoustics.